Determinants of Emotional Intelligence, Job Satisfaction and Organisational Citizenship Behaviour on Organisational Performance in the Malaysian - Suan, Chin Tee (2018)
The ever changing and dynamic global business environment has increased the level of difficulty for organisations not only to move upwards but to sustain. Organisations need to find a strategic asset which could push the organisation forward. The study uses the Resource-Based theory as its foundation. Based on the theory, the best asset for organisations to possess is an intangible asset. These intangible asset lies within the employees in the organisation. A successful organisation in the plastic manufacturing industry has been chosen. The organisation is one of the oldest and successful plastic manufacturing organisation in Malaysia. The study focused on 3 variables which has been suggested to determine performance, they are Emotional Intelligence, Job Satisfaction and Organisational Citizenship Behaviour. 110 executives took part in the study. The self-administered questionnaire was distributed to all of the executives. The results showed that Emotional Intelligence, Job Satisfaction and Organisational Citizenship Behaviour does play a role in the performance of an organisation. Based on the parallel multiple mediation analysis, it was found that Job Satisfaction has a higher indirect mediating effect in the relationship between Emotional Intelligence and Organisational Performance.